DISRUPSI LAYANAN KESEHATAN BERBASIS TELEMEDICINE: HUBUNGAN HUKUM DAN TANGGUNG JAWAB HUKUM PASIEN DAN DOKTER - Abigail Prasetyo; Dyah Hapsari Prananingrum (Refleksi Hukum: Jurnal Ilmu Hukum, 2022)
Technological developments from various aspects currently running in society are a reality, and the law must be able to regulate these changes. Technological developments also occur in health services, from conventional to telemedicine. Telemedicine is an electronic-based health service, so doctors and patients do not meet face-to-face. During the COVID-19 pandemic, telemedicine services are an alternative for patients to consult their doctors. This article describes the legal relationship and legal responsibility in telemedicine. The legal relationship between doctor and patient is created through a standard agreement; in this case, it is a therapeutic agreement. Therapeutic agreements still occur even though doctors and patients do not face each other directly. Regarding the form of accountability, in telemedicine, the absolute responsibility of doctors for their patients is known. In the end, it should be realized that there are still many weaknesses for doctors and patients and providers in telemedicine services.